2016
DOI: 10.1051/ita/2016017
|View full text |Cite
|
Sign up to set email alerts
|

Homing vector automata

Abstract: We introduce homing vector automata, which are finite automata augmented by a vector that is multiplied at each step by a matrix determined by the current transition, and have to return the vector to its original setting in order to accept the input. The computational power and properties of deterministic, nondeterministic, blind, non-blind, real-time and one-way versions of these machines are examined and compared to various related types of automata. A generalized version of the Stern-Brocot encoding method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A (real-time) k-dimensional deterministic homing vector automaton (DHVA(k)) is defined in [20] as being different from vector automata in two ways: (1) Homing vector automata do not read the right end-marker after reading the input, so there is no chance of postprocessing and, (2) instead of checking the status of the first entry, a homing vector automaton checks whether the complete current vector is identical to the initial vector or not. Formally, the transition function δ is defined as…”
Section: Vector Automata and Homing Vector Automatamentioning
confidence: 99%
See 4 more Smart Citations
“…A (real-time) k-dimensional deterministic homing vector automaton (DHVA(k)) is defined in [20] as being different from vector automata in two ways: (1) Homing vector automata do not read the right end-marker after reading the input, so there is no chance of postprocessing and, (2) instead of checking the status of the first entry, a homing vector automaton checks whether the complete current vector is identical to the initial vector or not. Formally, the transition function δ is defined as…”
Section: Vector Automata and Homing Vector Automatamentioning
confidence: 99%
“…In [21] it is shown that the non-context-free language POW r = {a 2 n b n |n ≥ 0} can be recognized by a DBHVA(2) Z 2×2 . It is left open whether there exists a 1NBHVA with integer entries recognizing POW r .…”
Section: Extended Finite Automata and Homing Vector Automata Defined mentioning
confidence: 99%
See 3 more Smart Citations